Seroprevalence and Risk Factors of Ornithobacterium rhinotracheale in Poultry Farms in Bangladesh - Ali, Md Zulfekar; Islam, Shariful; Hafez, Hafez M.; Javed, Muhammad Tariq (Journal of Advanced Veterinary Research, 2022)
Ornithobacterium rhinotracheale (ORT) is a bacterium that causing respiratory problems, growth retardation, high mortality, and drop in egg productions in poultry. The aim of the present investigation was to determine the seroprevalence and potential risk factors associated with the ORT infection in commercial poultry flocks in selected areas of Bangladesh. A total of 1920 serum samples were collected from 270 poultry farms including broiler (n=397), broiler breeder (n=430), layer (n=738), and a local breed namely Sonali (n=355) in Bangladesh were collected during 2017-2018 and the samples were tested for ORT antibodies using indirect Enzyme-Linked Immunosorbent Assay (iELISA). At individual level, the prevalence of ORT antibodies in examined samples was 39.05% (95% CI: 36.87-41.29) and at farm level, it was 50.74% (95% CI: 44.61-56.85). In multivariate Generalized Estimating Equation (GEE) analysis, sampling area, farm category, types of chicken biosecurity condition and types of drinker used were identified as positively correlated with potential risk factors (p<0.05) for the seroprevalence of ORT in poultry farms. Therefore, it could be concluded that ORT is prevalent among commercial poultry of Bangladesh. Proper biosecurity measures at farm level and vaccination of birds against the ORT are highly recommended.